(untitled) (American Journal of Islam and Society, 1992)
Introduction Islamic teachings envisage a balanced society achieved through the functioning of Islamic institutions. This paper visualizes three main institutions: ukhiwah, ‘adl, and ihsan. Ukhuwah (brotherhood) promotes the bonds of brotherhood, and ‘adl (justice) enforces a system of individual and social obligations. Islam stresses the importance of meeting one’s obligations, because each obligation has its corresponding right. Thus, an individual’s effort to meet hidher obligations leads to the fulfillment of everyone’s rights. This does not mean that Islam forbids one from demanding hidher rights, even though this demand does pose a problem related to human nature: an individual wants his/her rights and also some part of another person’s rights. Therefore, one group’s demand for its rights tends to encroach upon the rights of another group, which causes social friction and disorder. The institution of ihsan (benevolence) goes one step further: it exhorts individuals to forego their rights for the sake of others, which is considered an act of piety. This paper will study employer-employee relationships in the light of the three institutions mentioned above. A framework for conducting employer-employee relationships is formulated and is then used to determine, from the Islamic point of view, the proper wages. The findings of this paper show that an economically efficient and equitable wage structure can evolve within this framework and that such a wage structure would promote the parties’ mutual relationships which, in turn, would lead to industrial peace. The body of the paper is organized as follows: a review of the existing literature on the subject, the development of an Islamic framework for employer-employee relationships, a discussion of the Islamic approach to wage compensation, and some concluding remarks ...